Effectiveness of quality improvement: learning from evaluations. Issue 1 (1st March 2002) - Walshe, K; Freeman, T
Abstract : The effectiveness of many quality improvement interventions has been studied, and research suggests that most have highly variable effects which depend heavily on the context in which they are used and the way they are implemented. This has three important implications. Firstly, it means that the approach to quality improvement used in an organisation probably matters less than how and by whom it is used. Rather than taking up, trying, and then discarding a succession of different quality improvement techniques, organisations should probably choose one carefully and then persevere to make it work. Secondly, future research into quality improvement interventions should be directed more at understanding how and why they work—the determinants of effectiveness—rather than measuring whether they work. Thirdly, some element of evaluation should be incorporated into every quality improvement programme so that its effectiveness can be monitored and the information can be used to improve the systems for improvement.